The Influence of Progressive Muscle Relaxation and Mental Imagery-based Relaxation on Psychological Characteristics of Women with Unintended First Pregnancy during COVID-19 Pandemic: A Single-Blind Clinical Trial - Mansoureh Mokaberian; Houriyeh Dehghanpouri (Mashhad University of Medical Sciences, 2021)
Background & aim: Pregnancy is one of the most important stages in a women's life. Occurance of unintended first pregnancy due to changes in women's life-style following COVID-19 pandemic has led to more stress, anxiety, and uncertainty pregnant women. Therefore, the current research aspires to examine how progressive muscle relaxation intervention and imagery-based relaxation technique can affect the psychological characteristics of women with unintended first pregnancy during COVID-19 pandemic. Methods: This single-blind, parallel groups, pretest-posttest randomized controlled trial was conducted on 60 women with first unwanted pregnancy  who attended the urban clinics in Semnan, Iran in 2020, and were assigned to experimental and control groups. Tools for measurement included a demographic questionnaire as well as Depression, Anxiety, Stress Scale (DASS-21). In the experimental group, women were given 8 weeks of progressive muscle relaxation and imagery-based relaxation intervention; while women in the control group only received the routine care. One day before and one day after the intervention, DASS-21 was completed by the subjects.Results: The results of the multivariate analysis of covariance (MANCOVA) showed that after 8 weeks of intervention, the level of anxiety (P=0.0001), depression (P=0.0001) and stress (P=0.0001) decreased in the experimental group in comparison with the control group (P≤0.016). Conclusion: According to the results, it can be concluded that in order to improve the psychological status of women with unintended pregnancy, especially in the stressful conditions of COVID-19 disease, the relaxation techniques can be used as cost-effective and non-pharmacological approaches to build more emotional stability.